3360 sayılı il özel idaresi kanunu ve 5302 sayılı il özel idaresi kanununun karşılaştırılmalı analizi - Kutluk, Ersoy (My University, 2006)
Türk kamu yönetiminde, global dönüşüme paralel olarak gerçekleşen reform, il özel idarelerinin yapısında da önemli bir değişimi beraberinde getirmiştir. Bu süreçte, il özel idarelerinin uzun bir zamandır sahip olduğu yapıdan, gerek yönetim anlayışı gerekse idari uygulamalar açısından ayrıldığı görülmüştür. İl özel idareleri açısından son dönemde yaşanan en önemli değişim, 3360 sayılı İl Özel İdaresi Kanununun yürürlükten kaldırılıp, yerine 5302 sayılı İl Özel İdaresi Kanununun konulmasıdır. Yeni il özel idaresi kanunuyla, il özel idaresinin kuruluşu, organları, yönetimi, görev, yetki ve sorumlulukları ile çalışma usul ve esasları yeniden düzenlenmiştir. Bu kanun, il özel idareleri için birçok yeniliği de beraberinde getirmiştir. Bu çalışma ile il özel idarelerinin Türk kamu yönetimindeki yeri, hukuki dayanakları ve tarihsel arka planı incelenmiş; liberal politikalar bağlamında geçirdiği değişim süreci irdelenmiş; 5302 sayılı İl Özel İdaresi Kanunu ile ortaya çıkan yeni durum, 3360 sayılı İl Özel İdare Kanunu ile karşılaştırılmalı olarak analiz edilmiştir. Çalışmada, konunun oldukça yeni olmasından ötürü halen literatürde yerini almayan bazı hukuki düzenlemeler ilgili yerlerde verilmiştir. İncelemede, il özel idareleri ile ilgili teorik bilgiler yer alırken, mevcut alan araştırmalarından elde edilen veriler gerekli yerlerde sunulmuş; İstanbul İl Özel İdaresi’nde bürokratlarla ve meclis üyeleriyle yapılan görüşmelerle de çalışmanın pratik uygulamaları içeren kısımları desteklenmiştir.

The reform which took place parallely to global transformation in Turkish public administration brought a significant change in the structures of special provincial administrations. In this process, it is observed that the special provincial adminisrations have parted from the point of view of both in administrative understanding and administrative implementations for a long time. The most important change in the recent period from the point of view of special provincial administrations is the repealing of the Special Provincial Administrative Code numbered 3360 and promulgation of the Special Provincial Administrative Code numbered 5302. Through the new special provincial administrative code; the establishment, organs, administration, tasks, authorizations, responsibilities, working methods and Essentials were re-organized. This code has brought many novelties and changes for special provincial administrations. With this study, the place of the special provincial administrations in Turkish public administration, the legal basis and historical back ground are analyzed; the process of change discussed on the context of liberal policies; the new situation that arose through the Special Provincial Administrative Code numbered 5302 is analyzed in comparison with the Special Provincial Administrative Code numbered 3360. Because the topic is quite new, in this study some legal regulations which do not yet take part in the literature are given in related places. In the analysis, while the theoretical information regarding the special provincial administrations the information obtained from existing field researches are presented in relating places; through the interviews made with the bureaucrats and members of provincial council the parts of the study which consist the practical implementations of the study are supported.
Keywords: Kamu Yönetimi; Reform